Making sense of quality teaching and learning in higher education in Ethiopia: Unfolding existing realities for future promises - Tadesse, Tefera; Manathunga, Catherine; Gillies, Robyn (Journal of University Teaching and Learning Practice, 2018)
Current approaches for assessing the quality of teaching and learning in higher education focus solely on compliance and accountability, and use quantitative measures that serve as indicators of institutional effectiveness and efficiency, yet whether such approaches have linked to instructional activities or students learning in universities are not clearly known. Moreover, while quality is a complex and multifaceted construct, its measurement using qualitative evidence of actual teaching and learning is generally minimal. This study fills this gap by examining broadly the perceptions of a variety of stakeholders on the quality of teaching and learning, and assessment and review experiences in higher education in Ethiopia. Here the main focus was to acquire an understanding of the existing realities in relation to these issues. For this, the study uses a qualitative case study design collecting primary data from interviews with 4 senior managers and 4 education quality experts, and focus-groups with 6 teachers and 26 students, and exploring secondary sources. The findings of this study suggest that recent quality improvement efforts are piecemeal and more geared towards quality assurance than improvement. Most quality concerns, assessment and review practices seemed to result in little more than formal reporting and were implemented very haphazardly. It, therefore, appears from the analysis of the qualitative data that there have been less visible quality improvements and numerous challenges. This study recommends a functioning internal system, formative assessment, and the support and ownership of those who work in the sector as crucial for the implementation of quality improvement.